The Social and Behavioral Drivers of Exclusive Breastfeeding in Zimbabwe's Diverse Districts. - Chinofunga, Doroth; Julia, Mutambara; Titus, Moetsabi; Melody, Mapope; Jane, Kaifa (Papanda Publisher, 2025)
Exclusive Breastfeeding (EBF), is a practice where infants are fed solely breastmilk the first six months of life, without any food or drink, which is vital for infants’ optimal growth. In Zimbabwe, despite the recognized benefits of EBF, it continues experiencing low EBF rates. Literature indicates educational role in influencing breastfeeding behaviours yet often over looks the complex social- behavioural drivers that interact across various demographic groups. Therefore, this study addresses this gap by examining deeper social dynamics and cultural practices that shape breastfeeding practices. Participatory research design was used, with 600 participants from different age groups. Key informants included Government heads of departments, traditional leaders, community leaders, and NGOs, EBF doers and non-doers. Results show that mothers who exclusively breastfed for 6 months had good understanding of EBF benefits, exhibited interest, and used it as contraceptive. Positive experiences and skills were influenced by supportive figures. Finally, cultural practices like fontanelle rituals done during pregnancy. The study concludes that education on EBF benefits is crucial, self efficacy and online resources can further support EBF practices. It is recommended that future research focus on long term impacts of cultural practices such as fontanelle rituals on EBF adoption and duration.